2007
DOI: 10.1007/s11547-007-0155-3
|View full text |Cite
|
Sign up to set email alerts
|

Jaw osteonecrosis in patients treated with bisphosphonates: MDCT evaluation

Abstract: Jaw osteonecrosis is an established medical entity discovered in patients who have undergone treatment with bisphosphonates and dental extraction or other oral surgery. MDCT with multiplanar (MPR), volume rendering (VR) and three-dimensional (3D) reconstructions allows accurate assessment of affected bone structures, enabling early diagnosis and suitable treatment planning. Radiologists should be aware of the risk of osteonecrosis in patients treated with bisphosphonates and be able to distinguish it from othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The authors did note, however, that CT better demonstrated extent of changes, and cautioned that metastatic disease cannot be ruled out in the case of purely lytic lesions, as has been described by others (Bedogni et al , 2007). Milillo et al reported bone abnormalities in all 38 patients evaluated by CT; however, specific findings and how these related to prior panoramic radiographs were not described (Milillo et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors did note, however, that CT better demonstrated extent of changes, and cautioned that metastatic disease cannot be ruled out in the case of purely lytic lesions, as has been described by others (Bedogni et al , 2007). Milillo et al reported bone abnormalities in all 38 patients evaluated by CT; however, specific findings and how these related to prior panoramic radiographs were not described (Milillo et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a pathologic condition of bone, there are no established diagnostic radiographic criteria for BONJ. Several studies have reported various radiographic findings from panoramic films and computed tomography (CT) that include sclerosis, cortical surface irregularities, persistent extraction sockets, bone fragmentation (sequestration) and lytic or radiolucent changes (Marx et al , 2005; Chiandussi et al , 2006; Groetz and Al‐Nawas, 2006; Bianchi et al , 2007; Fullmer et al , 2007; Milillo et al , 2007). However, the frequency and consistency of these findings, and the relationship between clinical and radiographic signs remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…From the studies that staged BRONJ cases, the RF reported of BRONJ Stages 1 to 3 from panoramic radiography, CT, and CBCT included sclerosis, cortical surface irregularities, persistent extraction sockets, bone fragmentation (sequestrum), and lytic or radiolucent changes. [7][8][9][10][11]43,44 RF for the BRONJ stage 0 has been pointed as alveolar bone loss (not associated to chronic periodontal disease), trabecular bone alterations, persistent alveolar sockets, sclerotic changes of the lamina dura, and inferior alveolar canal narrowing. 5 From this point, the destructive bone changes have been often depicted as progressive, starting from the lamina dura and cortical plate, involving the alveolar bone and then progressing to the medullar bone, and finally affecting the entire cross-sectional area of the jaw bone.…”
Section: Radiographic Findings Under Antiresorptive Therapymentioning
confidence: 99%
“…Previous studies have reported RF from panoramic radiography, CT, and cone-beam CT (CBCT). [7][8][9][10][11] However, the frequency and consistency of these findings remain unclear. Based on these premises, the goal of this systematic review was to answer the following focused question: "Among patients receiving antiresorptive bone therapy, what is the prevalence of RF on the jaws?"…”
mentioning
confidence: 99%